2020
DOI: 10.1176/appi.ajp.2019.19010034
|View full text |Cite|
|
Sign up to set email alerts
|

Dose-Response Meta-Analysis of Antipsychotic Drugs for Acute Schizophrenia

Abstract: The dose-response relationships of antipsychotic drugs for schizophrenia are not well defined, but such information would be important for decision making by clinicians. The authors sought to fill this gap by conducting dose-response meta-analyses.Methods: A search of multiple electronic databases (through November 2018) was conducted for all placebo-controlled dose-finding studies for 20 second-generation antipsychotic drugs and haloperidol (oral and long-acting injectable, LAI) in people with acute schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
177
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(188 citation statements)
references
References 105 publications
6
177
2
3
Order By: Relevance
“…Although there was no significant difference in the primary outcome between LUR40 and LUR80, the effect size of LUR40 seems to be larger than that of LUR80. Dose‐response meta‐analysis of antipsychotic drugs for acute schizophrenia showed that the 95% effective dose of lurasidone was 147 mg/d 17 . Further studies are needed to investigate why LUR’s efficacy did not increase dose dependently in Japanese patients (eg, pharmacogenetics on drug response and drug metabolism).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant difference in the primary outcome between LUR40 and LUR80, the effect size of LUR40 seems to be larger than that of LUR80. Dose‐response meta‐analysis of antipsychotic drugs for acute schizophrenia showed that the 95% effective dose of lurasidone was 147 mg/d 17 . Further studies are needed to investigate why LUR’s efficacy did not increase dose dependently in Japanese patients (eg, pharmacogenetics on drug response and drug metabolism).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the uses of different statistical techniques and datasets, the dose-response relationships of lurasidone for overall psychotic symptoms found in a previous meta-analysis and this study were relatively similar 13 . Leucht and colleagues (2020) conducted their meta-analysis using a multivariate statistical technique to plot both metaanalysis estimates and their 95% CIs 41 .…”
Section: Discussionsupporting
confidence: 48%
“…Impaired connectivity of the auditory-related neural circuitry leads to altered self-monitoring, and misinterpretation of own thoughts as external voices (12,13). Considering their similar psychopathology and responsiveness to the antipsychotic treatment (4,14), we speculate that AVH in both mental conditions might be caused by disturbances in a common pathophysiological pathway, despite obviously distinct etiological origins of SZ and VLOSLP.…”
Section: Introductionmentioning
confidence: 94%